THE INFLUENCE OF PROFESSIONALISM AND ORGANIZATIONAL COMMITMENT WITH MEDIATION OF JOB SATISFACTION IN THE CONTEXT OF AUDIT QUALITY - Firdiyansyah, Indra; Ezky Tiyasiningsih; Nurul Yusyawiru; Hazriyanto; Edinur Ilham (Riau International Conference on Economics, Business and Accounting, 2024)
This study aims to determine the direct and indirect effects between Professionalism And Organizational Commitment With Mediation Of Job Satisfaction In The Context Of Audit Quality. The sample in this study were auditors at private universities in Batam City, totaling 178 respondents. Researchers used SEM (Structural Equation Modeling) with the software used, namely AMOS to process and analyze data. The results showed that organizational commitment and professionalism have a direct effect on job satisfaction, professionalism, organizational commitment and job satisfaction have no direct effect on audit quality, while professionalism has a direct effect on organizational commitment. on the indirect effect job satisfaction cannot mediate professionalism on audit quality and job satisfaction cannot mediate organizational commitment to audit quality, this is indicated by the parameter value above 0.05.